The Implementation of Temporary Endowment in Kuwait - Ab Rahman, Muhamad Firdaus; Amanullah, Muhammad (Al-Jami'ah: Journal of Islamic Studies, 2016)
Temporary waqf is a restricted endowment for a specific duration. This paper examines Kuwait Law of Waqf and the contemporary implementation of temporary waqf in Kuwait. The research shows that Kuwait law of waqf allowed the application of all types of waqf as temporary, the duration of waqf should not exceed sixty years and no more than two layers of generations. This paper proposes to encourage other Islamic countries to implement this concept of temporary waqf as an alternative benefit.[Konsep wakaf sementara adalah wakaf yang dibatasi masa berlakunya selama periode waktu tertentu. Makalah ini mendiskusikan Undang-Undang Wakaf Kuwait dan implementasi wakaf sementara di Kuwait. Penelitian ini menunjukkan bahwa perundang-undangan di Kuwait membolehkan penerapan wakaf sementara ini dalam semua jenis wakaf, dengan batasan tidak boleh melebihi 60 tahun dan melewati dua generasi. negara-negara Islam lainnya disarankan dapat menerapkan konsep wakaf sementara ini sebagai alternatif perluasan manfaat wakaf.]